Flow and Emotional Experience in Spirituality: Differences in Interactive and Coactive Collective Rituals. (July 2016) - Rufi, Sergi; Wlodarczyk, Anna; Páez, Darío; Javaloy, Federico
This study seeks to compare flow and emotional experience in interactive and coactive collective rituals. For such purpose, a correlational study was performed collecting self-report measures of flow, positive emotions, and social identity in three different social collective gatherings: the Sunday celebration of a Catholic mass ( N = 57), a Zen Buddhist meditation practice ( N = 50), and secular Sunday group activities ( N = 37). Results show the presence of flow in all three contexts, being higher in the interactive social situations (the Catholic mass and other Sunday group activities) than in the coactive one (the Zen meditation practice). Positive emotions are also higher in the interactive situations than in the coactive one. Regarding self-transcendent emotions, there is more inspiration in the Zen meditation practice and more hope in the Catholic mass. Flow and positive emotions are positively correlated in all three contexts. Specifically in the Zen meditation practice, flow, positive emotions, loss of self-consciousness, and social identity are positively correlated.